2022
DOI: 10.1177/0306624x211067089
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Senior Psychopathy: Informant Reports of Deceit and Antisocial Behavior in Multiple Types of Relationships

Abstract: A prevailing view among researchers and mental health clinicians is that symptoms of antisocial personality disorder (ASPD)/psychopathy decrease as affected individuals reach middle age. In the current investigation, informants were surveyed about the behavior of individuals who they believed showed traits of ASPD/psychopathy and were over the age of 50. A final sample of 1,215 respondents rated the index individuals according to the ASPD/psychopathy traits derived from the pre-publication first draft of the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Overall, the magnitude of the self-informant correlations reported in this research is consistent with results typically found in the broader personality literature (Beckmann et al, 2020; Connelly & Ones, 2010) and comparable with previously reported self-informant Dark Triad ratings (Hudek-Knezevic et al, 2021; Lämmle et al, 2021; McLarty et al, 2021; Miller et al, 2011). It is unsurprising there were mean self-informant differences in Dark Triad scores given informant reports can be influenced by informant type (romantic partner vs. work colleague), context (home vs. work; Andersen et al, 2022), and observability of the traits being measured (Connelly & Ones, 2010; John & Robins, 1993; Klonsky et al, 2002; Vazire, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the magnitude of the self-informant correlations reported in this research is consistent with results typically found in the broader personality literature (Beckmann et al, 2020; Connelly & Ones, 2010) and comparable with previously reported self-informant Dark Triad ratings (Hudek-Knezevic et al, 2021; Lämmle et al, 2021; McLarty et al, 2021; Miller et al, 2011). It is unsurprising there were mean self-informant differences in Dark Triad scores given informant reports can be influenced by informant type (romantic partner vs. work colleague), context (home vs. work; Andersen et al, 2022), and observability of the traits being measured (Connelly & Ones, 2010; John & Robins, 1993; Klonsky et al, 2002; Vazire, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly convincing is that, across the various papers included in the Special Issue, demonstration of these harms spanned different assessment methods (including clinical interviews, self-, and informant-reports), manifested as bi-directional effects in parent/child dyads (e.g., influence of parental psychopathic traits on adolescent children’s adjustment, Fanti & Lordos, 2021 ; influence of child callous-unemotional traits on aggression toward parents, Kuay et al, 2022 ), and emerged at different stages across the lifespan. This latter point may be particularly noteworthy, as it counters the widespread belief that harms associated with psychopathy decrease with age, and also stresses the importance of age-sensitive assessment of psychopathic traits (e.g., Andersen et al, 2022 ). These findings also support Lilienfeld et al, (2019) contention that what most specifically makes psychopathy a form of psychopathology is the degree to which it impacts the social adaptability of both self and others (see also Jurjako et al, 2022 ).…”
Section: The Interpersonal Impact Of Psychopathymentioning
confidence: 99%
“…To this end, while only two of the papers included in the Special Issue focused on forensic samples (and more specifically on treatment and recidivism; Polaschek et al, 2021 ; Rojas & Olver, 2022 ), all 10 papers have nonetheless offered a clear focus on the detrimental impacts that individuals with psychopathic traits can impart within society. Indeed, included manuscripts focused on the impact of psychopathy within romantic relationships (in both middle and older adulthood; Andersen et al, 2022 ; Forth et al, 2022 ; Uzieblo et al, 2022 ), within parent-child dyads ( Fanti & Lordos, 2022 ; Kuay et al, 2022 ), within the workplace ( Kranefeld et al, 2022 ; Stewart et al, 2022 ), and within society at large ( Jurjako et al, 2022 ). Across these studies, the significant, detrimental impact that individuals with heightened psychopathic traits impart is highlighted, not only for their victims, but also for their family, friends, and colleagues.…”
mentioning
confidence: 99%
“…According to these data, the prevalence of ASD is increasing, and the latest report published on 27 April 2018 indicated that the overall prevalence across 11 locations in the United States was 1 in 59 (approximately 1.68%). The CDC estimates that ASD is four times more likely to occur in males than in females [4,6]. Furthermore, most children with autism need lifelong care, and the lifetime expenditure for an individual with ASD with no intellectual disabilities is about USD 2 million to 2.4 million in the United States [7].…”
Section: Introductionmentioning
confidence: 99%